Strategic Management and Educational Dynamics of Islamic Boarding Schools in Banten - Anis Fauzi; Nana Suryapermana; Iman Ruhmawan (STAI Hubbulwathan Duri, 2022)
This study aims to understand the application of strategic management and dynamics in three Islamic boarding schools in Banten. This research method is qualitative research with a case study approach. Data was collected through observation, interviews, documentation, triangulation, field notes, and member verification. Data analysis was carried out using descriptive qualitative methods with deductive and inductive analysis techniques. The results showed that the strategic management carried out by these three Islamic boarding schools were as follows; prepare a system that can provide an exemplary role for all levels within the Islamic boarding school and all stakeholders in the Islamic boarding school; provide equal roles and responsibilities to human resources in Islamic boarding schools; organize student activities optimally; prepare a system that can provide an example for all levels within the Islamic boarding school environment and all stakeholders within the Islamic boarding school environment; provide equal roles and responsibilities to human resources in the cottage.